ANALISIS TINGKAT KEPUASAN PENGGUNA APLIKASI GRAB (STUDI KASUS : KOTA PRABUMULIH) - Nur Aini H (JSK ( Jurnal Sistem Informasi dan Komputerisasi Akuntansi ), 2021)
Currently we can see that the development of technology in various aspects is growing very rapidly. Grab application users are believed to be one of the solutions to help ease and help with daily work. In Prabumulih City, now there are applications that can help ease daily work. The purpose of this study was to determine the level of user satisfaction with the Grab application in Prabumulih City and the tools used were SPSS Statistics 2.4. The results showed that the usability variable was good. This can be seen from the Learnability indicator (Ability) getting a total average value of 4.12, Satisfaction getting a total average value of 4.04, Service interaction getting total average rating is 4.07, Error (error) gets a total average rating of 4.11.